Implementasi Pembelajaran Pendidikan Agama Islam Berbasis Multikulturalisme Terhadap Keharmonisan Antar Peserta Didik - Hidayat, Taupiq; Nst, Puli Taslim; Al-Husna, Khofifah Indah; Nst, Rabiah Al-Husna (Ikhtisar: Jurnal Pengetahuan Islam, 2024)
This research is motivated by a deep need to understand the impact of Islamic Religious Education (PAI) learning with a multicultural perspective on harmony between students. Meanwhile, the approach in this research uses field research, which explores the influence of Islamic Religious Education (PAI) learning with a multicultural perspective on strengthening harmony between students at SMP N. 1 Rao. Through descriptive qualitative research methods, data was obtained through participatory observation, interviews, and document analysis regarding 1) the level of students' understanding of multicultural-based PAI learning, 2) the role of teachers and students in learning, and 3) the positive and negative impacts of multicultural-based PAI learning. The research results show that multicultural-based PAI learning contributes significantly to social dynamics and relationships between students in the school environment. These findings provide in-depth insight into the role of PAI in strengthening harmony in multicultural schools, with practical implications for the development of more inclusive learning strategies.